The performance of geothermal passive heating and cooling for asphalt and concrete pavement. (July 2021) - Baumgärtel, Sebastian; Schweighofer, Julian A.V.; Rohn, Joachim; Luo, Jin
Abstract: Hydronic pavement heating and cooling applications have been well established to provide road safety over the past two decades. However, most of the systems run on asphalt, only a few are tested with concrete, and there rarely is a comparison between those two common materials in their heating and cooling performance. In this work, a field study was carried out using asphalt and concrete as pavement material for pavement heating and cooling under the climatic conditions of the city Erlangen, Germany. Both heating performance in winter and cooling performance in summer were tested with similar setups and a low inlet temperature of 10 °C. The results indicate that asphalt's heating performance is worse than that of concrete, showing slightly lower surface temperatures and limited snow melting capabilities. During heavy snowfall, concrete's surface remained snow-free, while asphalt's surface was covered under a thin layer of snow, indicating that snow is melted not fast enough. However, in summer, asphalt, due to its lower albedo, had a significantly higher energy output of 450 W/m 2 compared to 290 W/m 2 of concrete. Therefore, asphalt showed good cooling perfomance, compared to concrete. Thus, it is concluded that both materials have advantages and disadvantages in geothermal passive heating and cooling, which leave the decision on appropriate material to match the specific planned parameters and environmental requirements. Graphical abstract: Image 1 Highlights: Concrete and asphalt were field tested for hydronic heating and cooling. The thermal conductivity of the used material and the albedo of the surface are key to the heating and cooling performance. Under the field test conditions, both materials provided good heating capacity. Snow melting was achieved when the tested concrete was used. The tested Asphalt did not provide snow free surfaces. In summer, cooling performance of tested asphalt is significantly higher than concrete's.